Assistance in Religious Moderation Curriculum Design in the Digital Era Islamic Religious Education Courses in Salahuddin Pasuruan - Barizi, Ahmad; Isroani, Farida; Jamilah, Jamilah (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
The Interdisciplinary Study-Based Islamic Religious Education Doctoral Study Program conducts community service activities in the form of curriculum workshops based on religious moderation values at the Salahuddin College for Islamic Studies (STAIS), Pasuruan. The workshop is designed to assist in the curriculum development process, particularly for the Islamic Education subject and other courses based on religious moderation values. This community service project adopts the ABCD (Asset-Based Community Development) concept of community empowerment as its strategy. Material for the construction of higher education curricula, curricula based on religious modernization, and the local curriculum model of STAIS Pasuruan based on religious moderation and Islamic boarding schools were disseminated because of this project. The Islamic Religious Education of STAIS Pasuruan Study Program is expected to implement planned follow-up activities in the form of curriculum insertion practices.